Pengaruh Audit Tenure, Ukuran Kap, dan Umur Perusahaan terhadap Audit Report Lag dengan Komite Audit Sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Sisdiana, Awalliyah; Hariani, Swarmilah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze and obtain empirical evidence regarding the effect of audit tenure, KAP size, and company age on audit report lag with audit committee as moderating variable. This research design is descriptive and causal. The population in this study were property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2023. The research sample was determined using purposive sampling method and obtained a sample size of 52 companies downloaded through the official website www.idx.co.id. The research was conducted for 5 years so that 260 sample data were obtained. The type of data used is secondary data and the analysis method used to test the hypothesis in this study is multiple linear regression and moderation regression with SPSS software version 22. The contribution of this research is theoretical contribution, practical contribution, and policy contribution. The results of this study indicate that audit tenure and company age have a negative effect on audit report lag. In addition, the audit committee is able to moderate the effect of audit tenure and company age on audit report lag, but is unable to moderate the effect of KAP size on audit report lag.